(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The present researches consider is entitled Investigation of Academic Achievement of Urban and Rural Adolescent Students. Thus in this examination, the connection between Academic Achievement (AA) was inspected among adolescent students in urban and rural zones. Contrasts among these two groups with respect to the previously mentioned factors were noted. In the present examination the fundamental targets were 1.To explore the connection between’s AA among urban students. 2. To research the connection amongst’s AA and AF among rural students. 3. To think about AA crosswise over sex of urban students. 4. To look at AA crosswise over sexual orientation of rural students. 5. To think about AA crosswise over sexual orientation and territories of urban and rural students. The point of the present investigation is to center around investigation of academic achievements among auxiliary school students as for rural and urban region. The aggregate Random examples comprise of 30 students of rural territory and 30students of urban zone of Delhi city. The questionnaires arranged from Manual for Academic Achievement Motivation Test by Dr. T. R. Sharma was regulated as instrument for think about. The ’t’- Test was utilized to investigations the information. The elucidations of the outcomes demonstrate that there was no noteworthy mean contrast between academic achievements among auxiliary school students as for rural and urban territory.